Lessons in theory of change: CCAFS Southeast Asia Research for Development Workshop - Sebastian, Leocadio S.; Kristjanson, Patricia M.; Förch, Wiebke; Jost, Christine (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
In CCAFS we are building our research for development agenda using outcomes thinking targeted towards five CGIAR intermediate development outcomes (IDOs). Each of our Flagship research programs and regions are developing theories of change (TOCs), impact pathways (IPs), and monitoring and evaluation (M&E) systems. Our impact pathways are harmonized, contributing to an overall CCAFS pathway in which we are focused on catalysing behavioral changes in next-users (see box below) so that they create an enabling environment for the intermediate development outcomes (IDOs). In Southeast Asia we have involved our partners and next-users from the very beginning of the process, so that their voices and priorities form the foundation of the regional theory of change. We are learning from them, and with them co-developing our research agenda. We organized a workshop in December 2013 for CGIAR Centre partners to develop a preliminary impact pathway, including a regional vision, behavioral outcomes and target research outputs. This was followed by a workshop in March 2014 with partners and next-users in the region.